Regulated Tristetraprolin Overexpression Dampens the Development and Pathogenesis of Experimental Autoimmune Uveitis - Xu, Biying; Tang, Jihong; Lyu, Cancan; Wandu, Wambui S.; Stumpo, Deborah J.; Mattapallil, Mary J.; Horai, Reiko; Gery, Igal; Blackshear, Perry J.; Caspi, Rachel R. (Frontiers in Immunology, 2021)
Non-infectious uveitis, a common cause of blindness in man, is often mediated by autoimmunity, a process in which cytokines play major roles. The biosynthesis and secretion of pro-inflammatory cytokines are regulated in part by tristetraprolin (TTP), an endogenous anti-inflammatory protein that acts by binding directly to specific sequence motifs in the 3’-untranslated regions of target mRNAs, promoting their turnover and inhibiting synthesis of their encoded proteins. We recently developed a TTP-overexpressing mouse (TTPΔARE) by deleting instability motifs from the TTP mRNA, resulting in increased accumulation of TTP mRNA and protein throughout the animal. Here, we show that homozygous TTPΔARE mice are resistant to the induction of experimental autoimmune uveitis (EAU) induced by interphotoreceptor retinoid-binding protein (IRBP), an established model for human noninfectious ocular inflammation. Lymphocytes from TTPΔARE mice produced lower levels of the pro-inflammatory cytokines IFN-γ, IL-17, IL-6 and TNF than WT mice, but higher levels of the anti-inflammatory cytokine IL-10, and higher proportions of regulatory T-cells. TTPΔARE mice also produced lower levels of antibodies against the uveitogenic stimulus. Heterozygous mice developed EAU, cell responses and antibody production at levels intermediate between those of the homozygous TTPΔARE mice and WT controls. Eyes from TTPΔARE mice could develop EAU following adoptive transfer of activated wild type T cells specific to IRBP peptide 651-670. Also, naïve T-cells from TTPΔARE mice could be activated by antibodies to CD3/CD28. These data demonstrate that elevated systemic levels of TTP can inhibit the pathogenic processes of EAU, and suggest the possible use of TTP-based treatments in humans with uveitic conditions.